MENINGKATKAN KETERAMPILAN PEMBELAJARAN DARING BAGI GURU SMK MUHAMMADIYAH ADIWERNA KABUPATEN TEGAL - Hetika; Arief Zul Fauzi; Ririh Sri Harjanti; Dewi Kartika; Akmalus Sidqi (Politeknik Negeri Sriwijaya, 2022)
The Covid-19 virus that spreads in Indonesia has a tremendous impact on all fields, one of which is education. As an effort to prevent the spread of the Covid-19 virus, learning during the pandemic is encouraged to be done remotely or commonly referred to as online learning. The online learning process requires schools to adapt, and during the school adaptation process, teachers and students experience problems because the online/online learning process is different from face-to-face/offline learning. The problem of online learning is also experienced by activity partners, namely SMK Muhammadiyah Adiwerna. Specific problems with partners are difficulties in explaining the subject matter. Creativity in the delivery of distance learning materials can be increased by implementing training programs for teachers in the use of technology and information. Therefore, the community service team provides training in making learning videos using the Open Broadcaster Software (OBS) application. This activity is carried out in three stages. The first stage, the activity team discussed with partners related to the problems that occurred. The second stage, the activity team determines the theme of the activity and prepares the material for the activity. The third stage, the activity team conducts an evaluation. The results of the activity showed that there was an increase in the ability of participants to make video tutorials to support online learning. Keywords: online learning, open broadcaster software